Beethoven the Pianist - Skowroneck, Tilman (Cambridge Cambridge University Press, 2010)
The widely held belief that Beethoven was a rough pianist, impatient with his instruments, is not altogether accurate: it is influenced by anecdotes dating from when deafness had begun to impair his playing. Presenting a new, detailed biography of Beethoven's formative years, this book reviews the composer's early career, outlining how he was influenced by teachers, theorists and instruments. Skowroneck describes the development and decline of Beethoven's pianism, and pays special attention to early pianos, their construction and their importance for Beethoven and the modern pianist. The book also includes new discussions of legato and Beethoven's trills, and a complete annotated review of eyewitnesses' reports about his playing. Skowroneck presents a revised picture of Beethoven which traces his development from an impetuous young musician into a virtuoso in command of many musical resources.
Based on a doctoral dissertation of 2007, see elsewhere in the collection
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Composer; Pianist; Piano; Keyboard music; Organology; Historically informed performance